Antimicrobial Activity of Bacterial Strains Isolated from Macrotermes belli-cosus Termite Mound: Antimicrobial Activity of Bacterial Strains Isolated from Macrotermes bellicosus - Benewindé Joseph Sawadogo; Sandrine E T Hien; Dagoro Palé; Ynoussa Maïga; Mahamadi Nikièma; Iliassou Mogmenga; Yerobessor Dabiré; Cheik A T Ouattara; Aboubakar S Ouattara (Journal of Tropical Life Science, 2023)
Natural environments like termite mounds can be a reservoir for novel microbial strains and antimicrobial metabolite producers. Hence, this study aimed to investigate the antimicrobial activities of bacterial strains isolated from Macrotermes bellicosus (M. bellicosus) termite mound materials. These materials were sampled from active termite mounds in the Somgandé botanic reserve in Ouagadougou, Burkina Faso. The study collected sixty-three bacterial isolates and assessed their antimicrobial activity against several pathogenic bacteria (Bacillus subtilis, Escherichia coli, Micrococcus luteus, Pseudomonas aeruginosa and Staphylococcus aureus) and two pathogenic fungi (Aspergillus niger and Candida albicans). The dual culture and paper disc diffusion assays revealed that 10 isolates (5 bacteria and 5 actinobacteria) inhibited the growth of at least one pathogenic microorganism. In comparison, four isolates inhibited both Gram-positive and Gram-negative bacteria. Overall, isolates MBm2, MBm8 (bacteria), and MBm26 (actinobacterium) displayed better antibacterial- and antifungal activity against all tested pathogenic microorganisms. It is germane to indicate here that several typical bacteria and actinobacteria isolated from the M. bellicosus termite mound materials were good producers of antibacterial and antifungal agents. Thus, future studies could further characterize these isolates and optimize their growth for producing antimicrobial compounds. The bioactive compounds should also be identified for further biotechnological applications.